PRAKTEK MANAJEMEN LABA PADA PERUSAHAAN GO PUBLIC DI INDONESIA DENGAN PENDEKATAN LONG TERM DAN SHORT TERM ACCRUAL MODEL (Studi Empiris Pada Jakarta Islamic Index ( JII ) Periode 2004 –2010 ) - Heppy Purbasari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2013)
In the recent time, earning management is still in the controversial area, earning management practice viewed based on two different perspectives, first perspectives believed that it was a mal practices (negatives), however, the other perspectives tend to said it should did by management (positives). The aim of this study is to analyze the differentiation of the earning management practices on the company listed in Jakarta Islamic Index based on long and short termdiscretionary accrual approach. The result based on Wilcoxon signed rank test shown there is asignificant differentiation between long and short term discretionary accrual. Thus, in the earning management practices that found in the company listed on JII since 2004 – 2010, managementtend to increased earning on the long term discretionary accrual model (average 0,1868196) rather than short term discretionary accrual model (average -0,5880015).